2007
DOI: 10.1128/jvi.02091-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Coronavirus 229E Papain-Like Proteases Have Overlapping Specificities but Distinct Functions in Viral Replication

Abstract: Expression of the exceptionally large RNA genomes of CoVs involves multiple regulatory mechanisms, including extensive proteolytic processing of the large replicase polyproteins, pp1a and pp1ab, by two types of cysteine proteases: the chymotrypsin-like main protease and papain-like accessory proteases (PL pro s). Here, we characterized the proteolytic processing of the human coronavirus 229E (HCoV-229E) amino-proximal pp1a/ pp1ab region by two paralogous PL pro activities. Reverse-genetics data revealed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 67 publications
3
53
1
Order By: Relevance
“…As discussed recently by Catic et al [28], it remains to be shown if these enzymes truly act as deubiquitinating enzymes in vivo. In vivo, however, the SARS-CoV PLpro is part of nsp3 localized to the membrane-bound viral replicase complex [29]. Deubiquitination of host substrate(s) in the context of a SARS-CoV infection, however, remains to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed recently by Catic et al [28], it remains to be shown if these enzymes truly act as deubiquitinating enzymes in vivo. In vivo, however, the SARS-CoV PLpro is part of nsp3 localized to the membrane-bound viral replicase complex [29]. Deubiquitination of host substrate(s) in the context of a SARS-CoV infection, however, remains to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Human coronavirus NL63 (HCoV-NL63) PL1 pro processes Nsp1↓2 while the PL2 pro processes the other two cleavage sites, Nsp2↓3 and Nsp3↓4 (Table 2; Chen et al, 2007). Both PL1 pro and PL2 pro of HCoV 229E can cleave Nsp1↓2 and 2↓ 3 (Table 2); however, the PL1 pro is more efficient in cleaving Nsp1↓2 while the PL2 pro is more efficient with respect to the latter site (Ziebuhr et al, 2007). Some viruses, such as SARS-CoV, MERS-CoV, and IBV, comprise only one functional PL2 pro to process all three cleavage sites ( Table 2).…”
Section: Papain-like Protease 1 Domainmentioning
confidence: 99%
“…The homologous enzyme, PLP2, from the human coronavirus 229E, has been shown to be critical to 229E viral replication 13. In addition, recent studies have shown that human deubiquitinating enzymes are potential anticancer drug-design targets.…”
Section: Introductionmentioning
confidence: 99%